Vít Hloušek, Lubomír Kopeèek, Origin, ideology and transformation of political parties: East-Central and Western Europe compared, Ashgate Publishing Limited, Surrey 2010, ss. 238. - Heydrych, Jarosław (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2011)
abstrakt